2018
DOI: 10.3390/molecules24010062
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microwave Pretreatment on Micronutrient Contents, Oxidative Stability and Flavor Quality of Peanut Oil

Abstract: The purpose of the present study is to investigate the changes in extraction yield, physicochemical properties, micronutrients content, oxidative stability and flavor quality of cold pressed peanut oil extracted from microwave (MW) treated seeds (0, 1, 2, 3, 4, 5 min, 700 W). The acid value and peroxide value of extracted oil from MW-treated peanuts were slightly increased but far below the limit in the Codex standard. Compared with the untreated sample, a significant (p < 0.05) increase in extraction yield (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 35 publications
(84 reference statements)
2
27
0
Order By: Relevance
“…It was found through comparison that the flavor substances in EPOs mainly include alcohols, aldehydes, ketones, alkanes, alkenes, and furans, and the variety and content of flavor components in one EPO is different from each other ( Zhang et al, 2012 ). The volatile flavors of tea oil, olive oil, soybean oil, corn oil, peanut oil, sunflower oil, sesame oil, and rapeseed oil were compared using solid phase micro-extraction-mass spectrometry, and it was found that olive oil contained the largest amount of esters, and the other EPOs had high amounts of aldehyde ( Hu et al, 2018 ).…”
Section: Complexity Of the Chemical Composition Of Eposmentioning
confidence: 99%
“…It was found through comparison that the flavor substances in EPOs mainly include alcohols, aldehydes, ketones, alkanes, alkenes, and furans, and the variety and content of flavor components in one EPO is different from each other ( Zhang et al, 2012 ). The volatile flavors of tea oil, olive oil, soybean oil, corn oil, peanut oil, sunflower oil, sesame oil, and rapeseed oil were compared using solid phase micro-extraction-mass spectrometry, and it was found that olive oil contained the largest amount of esters, and the other EPOs had high amounts of aldehyde ( Hu et al, 2018 ).…”
Section: Complexity Of the Chemical Composition Of Eposmentioning
confidence: 99%
“…Peroxide value PV Oil content is one of the key indexes to evaluate the production efficiency of oil from oilseeds 35 . As can be seen from Table 1, the contents of the peanut oil extracted from dried peanut kernels obtained by solar radiation and hot air were between 46.67 and 47.24 , which showed no significant difference p 0.05 .…”
Section: Chemical Analysis Of Peanut Oil Extracted From Dried Peanut mentioning
confidence: 99%
“…Peroxide value PV measured the quantity of peroxides in the oil, which served as an indicator index of the primary oxidation product formation 16 . It was widely employed as a measure of oil oxidative rancidity 38 .…”
Section: Chemical Analysis Of Peanut Oil Extracted From Dried Peanut mentioning
confidence: 99%
See 1 more Smart Citation
“…With mechanized reaping, the whole peanut plant, including the seed pods, are removed from the soil before being dried (sun or hot-air) and then seed shelling (Arya et al, 2016;Nawade et al, 2018). Peanuts easily lipid oxidize and decompose during storage and transportation due to their high-fat level (>50%), and this influence their nutritional, agricultural and edible safety importance (Chukwumah et al, 2007;Liu et al, 2018;Hu et al, 2019;Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%